Analisis Jeda dalam Percakapan Laki-Laki dan Perempuan dalam Tanya Jawab tentang Pernikahan Mewah - Felicia Felicia (Jurnal Bahasa dan Sastra, 2022)
Marriage is one of the interesting topics to be discussed, especially among young people. Perception of marriage in modern times may differ from the views of marriage 10 or 20 years ago. This study analyzes conversations in interviews with male and female students of the Faculty of Cultural Sciences, University of Indonesia. In the interview process, the researcher found a gap in both male and female respondents. Weddings in Indonesia are generally carried out according to certain customs and cultures, so it is interesting to examine how young people in their 20s view marriage. The pauses studied in this study are in the form of interjections such as hmm, aaaa or silence. Silence is considered a pause if the respondent does not provide an answer within 1 second. The pauses that arise in discussions related to marriage can be an indication of the respondent's knowledge of the trends and customs that are followed. Therefore, the research problem raised in this study is the role of pauses in the interview process. This study aims to analyze the presence of pauses and compare it between male and female respondents. The data in this study were obtained by using the listening and recording methods without the researcher getting directly involved. Participants know that their conversation is being recorded. This study involved 3 participants, 1 male participant and 1 female participant as respondents, and 1 female participant as the questioner. The recording of questions and answers with participants was then processed using the ELAN tool and observed pauses between propositions. One of the findings of this study is that pauses appear as an indication of the transition from one proposition to the next.